Sebagai Potensi Sari Air Perasan Daun Alpukat (Persea americana) Sebagai Biolarvasida Culex quinquefasciatus - Rafif, Devina Yunizar; Marlik, Marlik; Ngadino, Ngadino; Sulistio, Irwan; Hermiyanti, Pratiwi (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Avocado leaves contain various compounds that are proven to cause death in Aedes aegypti larvae. In its use has limitations, namely the nature of the extract tends to cause turbidity in water, thus inhibiting the survival of Aedes aegypti larvae. In contrast to Aedes aegypti larvae, Culex sp larvae can live and develop well in dirty water. This study aims to assess the potential of avocado (Persea americana) leaf juice as a biolarvicide of Culex sp. The treatment consisted of five groups of avocado leaf juice concentrations, namely 0% (negative control), 2.5%, 5%, 7.5%, and 10%. Each using 20 Culex quenquefasciatus instar III larvae with replication 6 times. Mortality data of Culex sp larvae exposed to avocado leaf juice for 24 hours were analyzed using Anova test, Bonferroni test, and Probit test. The results showed that the mortality rate of larvae was 12,5%, 25%, 72,5%, and 92,5%, respectively. The Anova test showed that there was a significant difference between the concentrations of avocado leaf juice (p=0.000), the Bonferroni test showed that only the negative control (0%) and the 2.5% concentration, as well as the 2.5% and 5% concentrations, were not significantly different. The LC50 value obtained is 2.338%. It was concluded that avocado leaf juice has the potential as a biolarvicide against Culex sp.